PHOTOSYNTHESIS, TRANSPIRATION, STOMATAL CONDUCTANCE OF SOME MELON (CUCUMIC MELO L.) GENOTYPES UNDER DIFFERENT DROUGHT STRESS - Akhoundnejad, Yelderem; Daşgan, Hayriye Yıldız (PARLAR SCIENTIFIC PUBLICATIONS (P S P), 2020)
Drought is a major threat to sustain the crop production in the world. This study was conducted to determine the drought resistance andsensitivity of five melon genotypes, which have been previously tested at young plant stages. Water deficit treatments of the experimentincluded theirrigation at field capacity to maintain100% of the plant requirement (control), irrigation at 50% of the field capacity and no irrigation (0%). Photosynthesis, transpiration, intercellular CO2 concentration (Ci), stomatal conductivity, water use efficiency, membrane damage index, yield and leaf temperature of melon genotypeswere measured. Drought treatments caused significant differences in the parameters investigatedbetween the melon genotypes. Photosynthesis, transpiration, stomata closure and yield had significant correlations. The results indicated that Mln 4 is more sensitive and CU 179 is more tolerant melon genotypes in under drought stress conditions.
Keywords: Drought; Stress; Melon; Water deficit; Photosynthesis; Transpiration